Unveiling the nature of nonequilibrium effects in dielectrics - Silva, Igor Ricardo Filgueira e (2025)
This work presents a comprehensive theoretical model for describing the generation and trapping dynamics of nonequilibrium charges in dielectric materials under leakage effects, without requiring prior assumptions about the material’s specific type. As a result, it applies to nonpolar and non-ferroelectric systems that nonetheless exhibit hysteresis in their dielectric response. This emergent behavior arises from barrier energy distributions, voltage polarity effects, and asymmetries in charge transfer rates, providing new insights into mechanisms that can mimic ferroelectric-like responses in leaky dielectrics. A deeper understanding of these properties is crucial for advancing semiconductor devices, contributing to their improved efficiency, reliability, and miniaturization. Furthermore, the striking similarities between the effects described by the model and those observed in ferroelectric materials open new perspectives for innovative applications, including nonvolatile memories, advanced sensors, and novel electronic components. This dissertation also presents an analytical solution that corroborates experimental findings, providing a detailed spectral analysis of impedance and dielectric permittivity by modes. By unifying these two approaches within a single theoretical framework, this work offers a more rigorous methodology for characterizing dielectric materials and their transport properties. Beyond its relevance to dielectric characterization, the model has been successfully applied to the definition and realization of Mem-emitters – optoelectronic devices that modulate light emission through internal state variables. By demonstrating the link between dielectric polarization fluctuations and optical transition dynamics, this work establishes a theoretical foundation for the development of programmable light-emitting systems with potential applications in neuromorphic computing and adaptive photonic circuits. The results obtained suggest that this model provides a comprehensive description of charge dynamics and macroscopic dielectric responses, offering a novel perspective for investigating nonequilibrium effects in dielectrics. This theoretical foundation paves the way for future research in material science, semiconductor physics, and next-generation electronic and optoelectronic devices.